Pick-and-place Task with Manipulator by Modular Approach - Kim, Jeong-Jung; Kang, Sungchul; Lee, Woosub (2017 14TH INTERNATIONAL CONFERENCE ON UBIQUITOUS ROBOTS AND AMBIENT INTELLIGENCE (URAI), 2017)
A modular approach for a robot has various advantages such as flexibility, re-configurability, and cost reduction. In this paper, we present a pick-and-place task with our modular manipulation system which is currently under development. The system consists of hardware platform, motion engine and task recognition engine and those elements are integrated for executing the task.